TANTANGAN DAN ETIKA HUMAN CAPITAL MANAJEMEN DALAM PENGEMBANGAN MASYARAKAT ISLAM: INTEGRASI PRINSIP KEADILAN, INKLUSI DAN PRIVASI DATA - Muhamad Bisri Mustofa; M. Afif Anshori; Siti Wuryan; Fariza Makmun (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2026)
Human Capital Management (HCM) is a strategic approach in improving the quality of human resources in various sectors, including in the context of Islamic Community Development (PMI). However, its implementation faces complex ethical challenges, especially related to the principles of justice, inclusion, and data privacy. These challenges arise along with the increasing digitalization of empowerment programs, the use of big data, and the need to integrate Islamic values in managerial decision-making. This research uses the library research method, by examining various primary and secondary literature, including books on Human Capital Management, works by experts in Islamic Community Development, and relevant indexed journal articles. The analysis was carried out with a thematic approach to identify the ethical principles and challenges of HCM implementation in the context of Islamic societies. The results show that the integration of HCM in PMI requires ethical governance that emphasizes fairness in the distribution of opportunities, inclusion for vulnerable groups, and protection of data privacy as part of the social mandate. The principle of justice demands equitable access to training and capacity building; inclusion emphasizes the empowerment of women, people with disabilities, and poor groups; Meanwhile, data privacy is the main issue due to the use of digital reporting systems that are prone to leaks. Islamic literature shows that these three principles are in harmony with maqāṣid al-sharī'ah, especially hifz al-nafs, hifz al-'ird, and hifz al-māl. The discussion emphasized the importance of formulating an ethical model of HCM based on Islamic values, where transparency, accountability, and the protection of human dignity are the main foundations. The integration of Qur'anic ethics in HCM practice can strengthen the sustainability of PMI programs and increase public trust in implementing institutions. This study concludes that human capital management in the development of Islamic society must comprehensively consider ethical aspects. Justice, inclusion, and data privacy are not only modern managerial principles, but an integral part of Islamic ethics that must be implemented in every empowerment process. This study recommends the preparation of ethical guidelines for HCM based on Islamic values as a reference for institutions and stakeholders in carrying out the PMI program.